Peran Pengawas Minum Obat (PMO) berhubungan dengan Kepatuhan Minum Obat Pada Pasien Penderita TB Paru - Eva Marvia; Dina Fithriana; Agus Putradana; Rubiati Rubiati; Suhartiningsih Suhartiningsih; Antoni Eka Fajar Maulana (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2024)
Introduction: Tuberculosis is a chronic, infectious disease that is still a public health problem in the world, including Indonesia.Purpose: The aim of this research is to determine the role of medication-taking supervisors in medication-taking compliance in patients suffering from pulmonary TB.Method: the type of research used is correlational with a cross sectional approach. The population of this study was 35 pulmonary TB patients in the Santong Community Health Center working area and 35 people as a sample. The sampling technique used was total sampling. Data collection uses a questionnaire. Data analysis used the Spearman rank test.Results: The results of the study showed that the majority of supervisors took medication which supported 94.3% and 5.7% of supervisors took medication who did not support it. Respondents with high compliance were 85.7%, moderate compliance was 8.6% and low compliance was 5.7%. The results of statistical tests show that there is a relationship between the role of the medication-taking supervisor and compliance with medication-taking in patients suffering from pulmonary TB in the work area of the Santong Community Health Center with a rho value =.000 < α with a strong level of correlation with a correlation coefficient value of .661.Conclusion: Compliance with taking medication in patients suffering from pulmonary TB has increased with the role of supervisors taking medication.